Вікові особливості професійного вигорання вчителів в умовах воєнного стану - МАРІНІНА, Віталія; ТУЛЮПА, Віталія (Київський національний університет імені Тараса Шевченка, 2025)
Background. The relevance of studying professional burnout remains constant, as it depends on the tasks and conditions of professional activity, which change both with the development of the relevant field and society as a whole. The armed aggression of the Russian Federation against Ukraine determines the specificity of these conditions through increased responsibility for the safety of students, chronic stress, increased anxiety, and violation of the basic need for security and stability in the world. Under such conditions, age as a factor of professional burnout influences the peculiarities of actualizing life and professional experience, as well as adaptive capabilities. The purpose of this study is to determine the peculiarities of age-related determination of teachers' professional burnout during martial law. Methods. To carry out the aim and objectives of the study, the following methods were used: methodology for diagnosing professional burnout (K. Maslach, S. Jackson, adapted by N. Vodopianova), methodology ‘Coping behavior in stressful situations' (S. Norman, D. Endler, D. James, M. Parker; adapted version by T. Kryukova); correlation analysis with a scatter plot to establish a connection between the motivation of professional and pedagogical activity, methodology for assessing the motivation of professional and pedagogical activity (K. Zamfir, modified version of A. Rean) and correlation analysis from the scatter plot to establish the relationship between the components of professional burnout and age, experience, behavioral, and motivational characteristics. The sample consisted of 50 teachers aged 30 to 64. Results. At the stage of professional development in teachers aged 30 to 44, pronounced emotional exhaustion is accompanied by a reduction in intrinsic motivation for professional activity and an increase in external negative motivation, as well as the active use of an emotionally oriented coping strategy, which exacerbates the existing psychoemotional stress. The presence of reduced intrinsic motivation contributes to greater depersonalization. Seeking social support can prevent a decline in personal achievements among teachers in this age group. At the stage of professional realization in teachers aged 45 to 64 years, the use of a problem-oriented coping strategy helps prevent emotional exhaustion. The dominance of intrinsic motivation precludes the development of depersonalization. Extrinsic motivation, both negative and positive, mitigates the impact of reduced personal achievements, serving as a confirmation of the social significance of work, professional status, and a means of maintaining personal authority. Сonclusions. It has been found that the age-related peculiarities of teachers' professional burnout correspond in content to the stages of development of the subject of professional activity. Age is a cross-cutting determinant of professional burnout, as it mediates the relationship between the components of professional burnout and motivation, as well as coping strategies, thereby determining its specificity for different stages of professional development. The stage of professional activity is significant in terms of emotional exhaustion and depersonalization only for teachers aged 45 to 64 years, which makes it necessary to study personal characteristics and compare them with those of the age group from 30 to 44 years.

Вступ. Актуальність дослідження професійного вигорання не втрачає актуальності повсякчас, оскільки залежить від завдань та умов професійної діяльності, які змінюються як із розвитком відповідної сфери, так і суспільства загалом. Збройна агресія РФ проти України визначає специфічність цих умов через посилення відповідальності за безпеку учнів, хронізацію стресу, посилення тривожності, порушення забезпечення базової потреби в безпеці та стабільності світу. За таких умов вік як чинник професійного вигорання визначає особливості актуалізації життєвого та професійного досвіду, адаптаційних можливостей. Мета дослідження полягає у визначенні особливостей вікової детермінації професійного вигорання вчителів в умовах воєнного стану. Методи. Для реалізації мети та завдань дослідження використано: методику діагностики професійного вигорання (К. Маслач, С. Джексон, в адаптації Н. Водоп'янової), методику "Копінг-поведінка у стресових ситуаціях" (С. Норман, Д. Ендлер, Д. Джеймс, М. Паркер; адаптований варіант Т. Крюкової); методику оцінки мотивації професійно-педагогічної діяльності (К. Замфір, модифікований варіант А. Реана) та кореляційний аналіз з діаграми розсіювання для встановлення зв'язку між складовими професійного вигорання та віком, стажем, поведінковими та мотиваційними характеристиками. Вибірка склала 50 вчителів віком від 30 до 64 років. Результати. На стадії розвитку професіонала у вчителів віком від 30 до 44 років виражене емоційне виснаження супроводжується зниженою внутрішньою мотивацією професійної діяльності та вираженою зовнішньою негативною мотивацією, а також активним використанням емоційно-орієнтованої копінг-стратегії, що посилює наявне підвищене психоемоційне напруження. Наявність зниженої внутрішньої мотивації сприяє більшій вираженості деперсоналізації. Звернення за соціальною підтримкою перешкоджає розвитку редукції особистих досягнень у вчителів цієї вікової групи. На стадії реалізації професіоналізму у вчителів віком від 45 до 64 років використання проблемно-орієнтованої копінг-стратегії сприяє попередженню емоційного виснаження. Домінування внутрішньої мотивації перешкоджає розвитку деперсоналізації. Зовнішня мотивація, як негативна, так і позитивна, зменшують вираженість редукції особистих досягнень, виступаючи підтвердженням соціальної значущості праці, професійного статусу та засобом збереження особистого авторитету. Висновки. Встановлено, що вікові особливості професійного вигорання вчителів відповідають за змістом стадіям розвитку суб'єкта професійної діяльності. Вік є наскрізною детермінантою професійного вигорання, оскільки опосередковує зв'язок складових професійного вигорання з мотивацією та копінг-стратегіями, визначаючи його специфіку для різних стадій професійного розвитку. Cтаж професійної діяльності є значущим щодо емоційного виснаження та деперсоналізації лише для вчителів віком від 45 до 64 років, що актуалізує необхідність дослідження особистісних властивостей та порівняння їх з показниками вікової групи від 30 до 44 років.
Keywords: age; professional burnout; coping strategy; motivation; length of service; professional development; вік; професійне вигорання; копінг-стратегія; мотивація; стаж; професійний розвиток